Mucormycosis of left maxilla: A case report and review - Poovaraghavan, J (Indian Journal of Case Reports, 2024)
Mucormycosis is an angioinvasive infection caused by fungi of the Zygomycetes order. Rhizopus is the main pathogen responsible for 90% of cases of cerebral mucormycosis. The term rhinocerebral mucormycosis should be used only in the face, palatal, orbital, paranasal sinus, or brain area. Here, we present the case of a 42-year-old man who presented with complaints of pain and swelling in relation to the left upper back tooth region for the past 20 days. In this case, the patient was immunocompromised due to type II diabetes, as well as COVID hospitalization. This case enlightens the investigation, as well as the management protocol followed by post-operative rehabilitation. Early diagnosis and prompt treatment can significantly reduce the morbidity and mortality of these deadly fungal infections.